EDUKASI KEAMANAN PANGAN JAJANAN ANAK SEKOLAH DENGAN POLA SAH MENGGUNAKAN MODEL BIOPSIKOSIAL - Sulistiyorini, Desy; Purnamasari, Eka Rokhmiati Wahyu (LPPM Universitas Nusa Mandiri, 2025)
Many school children still have limited knowledge about the safety of snack foods, causing them to choose snacks based on taste without considering the ingredients. To facilitate nutrition education for school children, instructional media in the form of PowerPoint slides were used. The snakes and ladders game method is highly suitable for school-aged students because it is interactive and enjoyable. The aim of this community service activity was to provide education on PJAS (school snacks) safety using the SAH approach (Fresh, Safe, and Hygienic) with the Biopsychosocial model. The method applied was lectures supported by PowerPoint slides. Based on the results of questionnaires regarding students' knowledge about PJAS safety, pre-test and post-test scores were obtained. Data were collected through questionnaires and analyzed using the Wilcoxon Signed Rank Test. The analysis showed an increase in students' knowledge about snack food safety after the intervention. Statistical analysis using the Wilcoxon Signed Rank Test resulted in p = 0.000 (p < 0.05), indicating a significant improvement in students' knowledge and attitudes between pre-test and post-test. Thus, PJAS food safety education using the Biopsychosocial model approach was proven effective in improving students' knowledge and attitudes regarding snack food safety.